Clinical management of cystic echinococcosis: state of the art and perspectives - Stojković, Marija; Weber, Tim; Junghanss, Thomas (Current opinion in infectious diseases, 2018)
Purpose of review: This review draws attention to patients with cystic echinococcosis migrating from highly endemic to non-endemic countries with limited experience in cystic echinococcosis management, to ultrasound-based cyst staging, and to the WHO cyst classification as a powerful, to date underused tool to triage patients into the four currently available treatment modalities.Recent findingsIn non- and low-prevalence countries, cystic echinococcosis is often misclassified. Differential diagnoses, such as simple cysts and other benign and malignant space-occupying lesions, have similar appearances on imaging. Serology is confirmatory but often disappointing due to sensitivity and specificity problems. There is increasing confidence in assigning uncomplicated cystic echinococcosis cysts to the four treatment modalities [drug treatment (benzimidazoles), percutaneous methods, surgery, watch and wait] on the basis of cyst stage (WHO cyst classification), size and location. However, current best practice is still not widely implemented outside cystic echinococcosis treatment centres, and further consolidation is needed by well-designed clinical trials. Recently published long-term follow-up studies have shown that patients with inactive cyst stages CE4 and CE5 benefit, especially since they do not need any treatment at all if they have not received prior benzimidazole or percutaneous therapy. Instead, cysts that have reached cyst stages CE4 and CE5 through drug treatment do need careful follow-up as they often relapse. Surgical procedures in which the cysts are opened and percutaneous approaches require very careful control of cyst content spillage to the peritoneum, pleura and intravascularly to prevent dissemination - a still too often neglected issue with severe consequences for patients.SummaryThough a neglected disease with predominantly expert-opinion-based treatment strategies, cystic echinococcosis patients can greatly benefit from interdisciplinary management in cystic echinococcosis treatment centres and cyst-stage-based assignment of treatment modalities. Increased suspicion for cystic echinococcosis in migrants from endemic to non-endemic countries is urgently needed at the current level of global mobility.
Gesehen am 17.04.2020